2017
DOI: 10.1177/1558944716668844
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Ossification After the Arthroscopic Treatment of Lateral Epicondylitis

Abstract: To our knowledge, we present the first case of HO development after elbow arthroscopy for lateral epicondylitis. As the use of elbow arthroscopy continues to grow, there is a need for identification of the risk factors and primary prophylaxis for HO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…To date, there have been 8 case reports on HO after arthroscopic procedures of the elbow. 2,24,32,35,36,51,74,85 Gofton and King 32 reported on a 47-year-old farmer who developed HO anteriorly and posteriorly to the distal humerus after arthroscopic loose body removal. At 4 years postoperatively, the patient underwent an open debridement and capsulectomy for residual stiffness and recurrent locking sensations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there have been 8 case reports on HO after arthroscopic procedures of the elbow. 2,24,32,35,36,51,74,85 Gofton and King 32 reported on a 47-year-old farmer who developed HO anteriorly and posteriorly to the distal humerus after arthroscopic loose body removal. At 4 years postoperatively, the patient underwent an open debridement and capsulectomy for residual stiffness and recurrent locking sensations.…”
Section: Resultsmentioning
confidence: 99%
“…After excision of the mature lesion and anterior capsular release, the patient regained full range of motion and returned to competitive pitching. Desai et al 24 presented a case of HO after arthroscopic debridement of lateral epicondylitis in a former collegiate basketball player. Early HO anterolateral to the lateral epicondyle was found on radiographs 7 weeks postoperatively, and he underwent open HO excision with repair of the common extensor origin 11 weeks later, with a single 700-cGy dose of adjunctive radiation therapy on the day of surgery.…”
Section: Resultsmentioning
confidence: 99%
“…4) Moderate activity: Clinical trials have shown that joint loosening during inactive ectopic ossification and complete maturation can effectively reduce ossification and help joint activity. Furthermore, in a rabbit model of trauma-induced HO, forced fixation of the animal's body aggravated the occurrence of HO [104]. This finding indicates that after the soft tissue is traumatized and subjected to longterm compression, tissue hypoxia promotes HO due to poor blood circulation.…”
Section: ) Nonsteroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 92%
“…Anteromedial, anterolateral Complete permanent posterior interosseous nerve palsy (transected) Anterolateral Dumonski et al 9 Severe permanent UN palsy (transected) Proximal medial Sodha et al 10 HO development impeding ROM, required open excision Posterior and posterolateral Park et al 11 Transient radial nerve palsy Proximal anterolateral Gay et al 12 Complete permanent UN palsy (transected) Proximal anteromedial Hughes and Hildebrand 13 HO development impeding ROM, required open incision Dexel et al 14 Transient aseptic subcutaneous emphysema Carafino et al 15 Complete permanent posterior interosseous nerve (PIN) Proximal anterolateral Carafino et al 15 Partial medial nerve (sensory) injury Proximal anteromedial Murphy et al 16 Severe permanent median nerve (MN) palsy (transected) Kinkartz et al 17 Postarthroscopic chondrolysis Mercer et al 18 Radial nerve (RN) palsy (laceration) Proximal anterolateral Desai et al 19 HO Excessive traction, cross-body adduction, lateral positioning and repetitive tourniquet inflation/ deflation should be avoided; management of modifiable risk factors (smoking cessation, diabetes, obesity, HTN); consider chemical prophylaxis in higher risk patients tourniquet time are not uncommon in this setting. 33 Thus, time of tourniquet inflation must be monitored similar to other procedures.…”
Section: References Complications Portalmentioning
confidence: 99%